The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12877-015-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and preferences towards screening for dementia: a systematic review of the literature

Abstract: BackgroundPopulation screening might provide a mechanism to enable early detection of dementia. Yet the potential benefits, harms or acceptability of such a large-scale intervention are not well understood. This research aims to examine the attitudes and preferences of the general public, health care professionals, people with dementia and their carers towards population screening for dementia.MethodsA systematic review of the international literature was undertaken. A search of fifteen bibliographic databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 42 publications
5
84
0
Order By: Relevance
“…This might be because GPs are the health professionals with whom the vast majority of the elderly population has a regular and long‐term contact (Miele et al, ), and therefore they might be much more comfortable seeking help from them with the justification that they are doing so as part of the routine health examinations. Despite this preference, it should be noted that till today there is no evidence supporting population screening for dementia (Martin et al, ). Thus, cognitive function should continue to be assessed by GPs only when cognitive decline or impairment is suspected, reported by patient or others, or where directly observed by the clinician, and not as a routine practice when none of these apply.…”
Section: Discussionmentioning
confidence: 99%
“…This might be because GPs are the health professionals with whom the vast majority of the elderly population has a regular and long‐term contact (Miele et al, ), and therefore they might be much more comfortable seeking help from them with the justification that they are doing so as part of the routine health examinations. Despite this preference, it should be noted that till today there is no evidence supporting population screening for dementia (Martin et al, ). Thus, cognitive function should continue to be assessed by GPs only when cognitive decline or impairment is suspected, reported by patient or others, or where directly observed by the clinician, and not as a routine practice when none of these apply.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies were identified which specifically explored 'who' should deliver screening programmes for people with dementia [12,17,25,26,27,28,29,30,31].…”
Section: Who Should Provide Early Diagnosis Of Dementia In Primary Care?mentioning
confidence: 99%
“…Martin et al [31] uniquely, explored the issues around dementia screening with patients and the public. In their interviews patients largely felt that clinicians should be qualified to undertake the assessment and therefore training was critically important.…”
Section: Who Should Provide Early Diagnosis Of Dementia In Primary Care?mentioning
confidence: 99%
See 2 more Smart Citations